Inhibitory potency of some methoxyphenyl derivatives compounds on class mu GST activity in vitro - Sudibyo Martono (Indonesian Journal of Pharmacy, 2005)
Methoxy phenyl derivative’s compounds i.e. curcumin, ferulic acid, and indomethacin have been reported to have inhibitory effects on rat’s liver glutathione S-transferases (GST) activity. Vaniline and ferulic acid have been known as degradation products of curcumin, and still have methoxy phenyl groups on the structures. Until the recent years, there is no information concerning the influences of methoxy phenyl derivative’s compounds i.e. vaniline, dimethylcurcumin and ethyl-p-methoxycinnamate on GST-activity. The aim of this research is to study the correlation of the inhibitory activity of class mu GST isolated from uninduced and phenobarbital-induced rat liver cytosol by curcumin, dimethylcurcumin, vaniline, indomethacin, ethyl pmethoxycinnamate, and ferulic acid. GST activity was measured spectrophotometrically on the conjugation of DCNB and GSH. The results showed that the inhibitory activity of mu class GST in uninduced or phenobarbital-induced rat liver GST were decreasing as follow : curcumin, dimethylcurcumin, vaniline, indomethacin, ethyl p-methoxycinnamate, and ferulic acid.Key words: methoxyphenyl derivative’s compounds, glutathione S-transferases activity.